Climate@Work - Lipsig-Mummé, Carla (Labour in Canada (Halifax, N.S.), 2013)
Climate change is having an increasingly significant impact on work in Canada, and the effect climate change has, and will continue to have, on work concerns many Canadians. However, this fact has not been seriously considered either in academic circles, in the labour movement nor especially by the Canadian government. Climate@Work addresses this deficit by systematically tackling the question of the impact of climate change on work and employment and by analyzing Canada’s conservative silence towards climate change and the Canadian government’s refusal to take it seriously.--Publisher's description. Contents: Introduction. Section 1: Contexts.Changing Patterns in the Literature of Climate Change and Canadian Work: The Research of Academics, Government and Social Actors / Elizabeth Perry -- Climate, Work and Labour: the International Context / Carla Lipsig-Mummé --International Trade Agreements and the Ontario Green Energy Act: Opportunities and Obstacles / Stephen McBride & John Shields. Section 2: Sectors. The Impact of Climate Change on Employment and Skills Requirements in the Construction Industry / John O’Grady -- Climate Change and Labour in the Energy Sector / Marjorie Griffin Cohen & John Calvert -- The Transportation Equipment Industry / John Holmes, with Austin Hracs -- The Forestry Industry / John Holmes -- Tourism, Climate Change and the Missing Worker: Uneven Impacts, Institutions and Response / Steven Tufts -- Climate Change and Work and Employment in the Canadian Postal and Courier Sector / Meg Gingrich, Sarah Ryan & Geoff Bickerton. Includes bibliographical references (pages 177-196).
Keywords: Canada. Climatic changes; Climatic changes; Economic aspects; Economic aspects. Climatic changes; Government policy